An Approach to Business Workflow Software Architectures: A Case Study for Bank Account Transaction Type Prediction - Calli, Fatma Gizem; Ayyildiz, Cagdas; Acikgoz, Berke Kaan; Aktas, Mehmet S. (SPRINGER INTERNATIONAL PUBLISHING AG, 2022)
Today, practically every bank's computer system can automatically categorize transactions. If someone uses their debit/credit card to buy groceries or clothing, they can see the sort of expense on their user account in seconds. Even though banks provide this level of categorization for individual users, there is no categorization solution for accounting systems. In this article, the main objective is to design and develop a business workflow that can predict bank account transaction types. Various machine learning and deep learning algorithms are used to accomplish this purpose. In the prototype implementation, Support Vector Machines, Random Forest, Long Short-Term Memory Networks, and Frequent Pattern Growth algorithms are used, and the prediction successes of these techniques are analyzed.
Keywords: Electronic bank transaction categorization; Electronic bank transaction prediction; Association mining rules; Deep learning; Machine learning; LSTM; FP-Growth; CLASSIFICATION; Computer Science; Science & Technology - Other Topics